Association between polyvascular disease and clinical outcomes in patients with cardiogenic shock: Results from the RESCUE registry. (15th September 2021) - Jang, Woo Jin; Park, Ik Hyun; Yang, Jeong Hoon; Chun, Woo Jung; Oh, Ju Hyeon; Park, Yong Hwan; Ko, Young-Guk; Yu, Cheol Woong; Kim, Hyun-Joong; Kim, Bum Sung; Lee, Hyun Jong; Jeong, Jin-Ok; et al.
Abstract: Background: Clinical implications of systemic atherosclerosis in patients with cardiogenic shock (CS) remain unclear. This study investigated the association between polyvascular disease (PVD) and clinical outcome in CS patients. Methods: A total of 1247 CS patients was enrolled from the RESCUE registry, a multicenter, observational cohort between January 2014 and December 2018. They were divided into two groups according to presence of PVD, defined as ≥2 coexistence of coronary artery disease, peripheral arterial disease, or cerebrovascular disease. Primary outcome was all-cause death during 12 months of follow-up. Results: 136 (10.9%) patients were diagnosed with PVD. The risk of 12-month all-cause death was significantly higher in the PVD group than in the non-PVD group (54.4% versus 40.4%, adjusted hazard ratio [HR] 1.31, 95% confidence interval [CI] 1.02–1.69, p  = 0.034). There was a significant interaction between PVD and vasoactive inotropic score (VIS) ( p for interaction = 0.014). Among the 945 patients with VIS <84, PVD was associated with a higher risk of 12-month all-cause death (unadjusted HR 1.77, 95% CI 1.30–2.41, p  = 0.030); among the 302 patients with VIS ≥84, the incidence of 12-month all-cause death was similar between the PVD and non-PVD groups (unadjusted HR 1.03, 95% CI 0.68–1.56, p  = 0.301). Conclusions: Presence of PVD was associated with 12-month all-cause mortality in patients with CS, especially for less severe forms of CS patients with VIS <84. Clinical trials.gov number: NCT02985008 Highlights: Polyvascular disease was associated with higher mortality in cardiogenic shock. Prognostic role of polyvascular disease was notable in less severe cardiogenic shock. Polyvascular disease was related to poor prognosis in shock requiring vasopressors.